A polyamide material and a method for producing the same

CN117402490BActive Publication Date: 2026-10-09CATHAY BIOTECH INC +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210797032.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-06
Publication Date
2026-10-09
Estimated Expiration
2042-07-06

AI Technical Summary

Technical Problem

[0005]本发明为了解决现有聚酰胺材料由于熔体粘度和强度较低,熔体流变性能差,难以满足发泡材料要求的缺陷,提供了一种以生物基聚酰胺树脂为基体的聚酰胺材料,原料单体来源于植物,具有低碳、可持续发展特征,且单体生产供应稳定,具备规模化潜力,材料性能优异,且熔体强度和粘度显著高于常规的聚酰胺材料,满足发泡材料的要求,极大的扩展发泡材料的应用领域,具有很高的商业化价值

Benefits of technology

[0049] This invention uses bio-based polyamide resin as raw material. By chain extension modification, the molecular weight of polyamide is increased, the molecular weight distribution is broadened, and the degree of chain segment branching is increased, thereby obtaining a polyamide material with high melt strength and viscosity, which meets the requirements of foaming materials. At the same time, the high bio-based content of the polyamide resin is beneficial to reducing energy consumption and meets the needs of low-carbon economy and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003732524550000141
    Figure BDA0003732524550000141
  • Figure BDA0003732524550000151
    Figure BDA0003732524550000151
Patent Text Reader

Abstract

The application relates to the technical field of high polymer materials, and discloses a polyamide material and a preparation method thereof, wherein the polyamide material comprises the following components in parts by weight: 85-98 parts of a bio-based polyamide resin, and 0.5-5 parts of a chain extender; the bio-based polyamide resin is formed by pentanediamine (A) and dicarboxylic acid components (B), and the total of the components (A) and (B) is 100 mol%; wherein the dicarboxylic acid components (B) are composed of the following components: (B1) 0-100 mol% of adipic acid, (B2) 0-100 mol% of terephthalic acid, and (B3) 0-100 mol% of aliphatic dibasic acid, and the total of (B1), (B2) and (B3) is 100 mol%. The application improves the molecular weight of the polyamide by chain extension modification, widens the molecular weight distribution, increases the chain segment branching degree, obtains the polyamide material with high melt strength and viscosity, meets the requirements of the foaming material, expands the application field of the foaming material, and has high commercial value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a polyamide material and its preparation method. Background Technology

[0002] Foam materials, due to their abundant internal foam structure, possess properties such as lightweight, buoyancy, insulation, and cushioning, making them crucial for energy conservation, emission reduction, and lightweight development. Foam materials made from polystyrene, polyethylene, and polyurethane are widely available on the market. However, foams made from these materials often suffer from insufficient mechanical properties and low chemical resistance.

[0003] Polyamides are widely used due to their high strength, chemical resistance, and excellent oil resistance. However, conventional polyamides have low tensile viscosity, melt viscosity, and strength during continuous melt extrusion foaming, resulting in poor melt rheological properties that make them difficult to meet the requirements of foamed materials.

[0004] Therefore, developing a new polyamide material that meets the foaming requirements can greatly expand the application fields of foamed materials and has high commercial value. Summary of the Invention

[0005] To address the shortcomings of existing polyamide materials, which suffer from low melt viscosity and strength, poor melt rheological properties, and difficulty in meeting the requirements of foamed materials, this invention provides a polyamide material based on bio-based polyamide resin. The raw material monomers are derived from plants, exhibiting low-carbon and sustainable development characteristics. Furthermore, the monomer production and supply are stable, possessing large-scale potential. The material exhibits excellent performance, with melt strength and viscosity significantly higher than conventional polyamide materials, thus meeting the requirements of foamed materials. This greatly expands the application fields of foamed materials and has high commercial value.

[0006] This invention provides a polyamide material comprising the following components in parts by weight: 85-98 parts of bio-based polyamide resin and 0.5-5 parts of chain extender; the bio-based polyamide resin is formed from pentanediamine (A) and dicarboxylic acid component (B), wherein the total of components (A) and (B) is 100 mol%; wherein the dicarboxylic acid component (B) is composed of the following components: (B1) 0-100 mol of adipic acid, (B2) 0-100 mol of terephthalic acid, and (B3) 0-100 mol of aliphatic dicarboxylic acid, wherein the total of (B1), (B2), and (B3) is 100 mol%.

[0007] In some specific embodiments, the dicarboxylic acid component (B) is composed of the following components: (B1) 10-90 molar proportion of adipic acid, (B2) 10-90 molar proportion of terephthalic acid, and (B3) 0 molar proportion of aliphatic dicarboxylic acid.

[0008] Preferably, the dicarboxylic acid component (B) comprises: (B1) 40-90 mol% adipic acid, (B2) 10-60 mol% terephthalic acid, and (B3) 0 mol% aliphatic dicarboxylic acid. That is, the dicarboxylic acid contains 40-90 mol% adipic acid and 10-60 mol% terephthalic acid or a derivative thereof, where the percentages are molar percentages.

[0009] Preferably, the molar ratio of adipic acid to terephthalic acid is 1:(0.1-1.5). For example, it can be 1:(0.35-0.55), such as 1:0.45; it can be 1:(0.55-0.85), such as 1:0.72; or it can be 1:(0.85-1.2), such as 1:1.05.

[0010] In some specific embodiments, the bio-based polyamide resin is formed from pentanediamine and dicarboxylic acid, wherein the molar ratio of pentanediamine to dicarboxylic acid is (1-1.05):1, for example 1.05:1.

[0011] In some specific embodiments, the preparation method of the bio-based polyamide resin includes the following steps: preparing a polyamide salt solution by mixing pentanediamine, dicarboxylic acid and water, and heating the polyamide salt solution to polymerize it to obtain the bio-based polyamide resin.

[0012] In some specific embodiments, the bio-based polyamide resin includes the following steps: (1) Under a nitrogen or inert gas atmosphere, water, pentanediamine, terephthalic acid or its derivatives, and adipic acid are mixed to prepare a polyamide salt aqueous solution with a concentration of 30-75 wt%; (2) The polyamide salt aqueous solution is transferred to a polymerization apparatus (e.g., a polymerization kettle), heated under a nitrogen or inert gas atmosphere to raise the temperature of the reaction system to 230-310°C and the pressure to 0.7-2.5 MPa, and maintained for 60-180 minutes; then, the pressure is reduced to atmospheric pressure within 30-120 minutes by venting, while the temperature is raised to 260-340°C; vacuum is applied to reduce the pressure to -(0.02-0.08) MPa and maintained for 30-120 minutes to obtain a melt; (3) The melt is stretched and granulated to obtain the bio-based polyamide resin PA56T.

[0013] In some specific embodiments, the relative viscosity of the bio-based polyamide resin PA56T is 2.05-2.65, and the melting point is 260-330℃. The relative viscosity is determined using the Ubbelohde viscometer method with concentrated sulfuric acid (96% concentration).

[0014] In some specific embodiments, the bio-based polyamide resin PA56T has a relative viscosity of 2.24-2.45 and a melting point of 270-300℃.

[0015] In some specific embodiments, the pentanediamine is of chemical origin or renewable biomass origin, preferably 1,5-pentanediamine of biological origin. In this invention, the 1,5-pentanediamine of biological origin is prepared by a biological method; the biological method includes production using bio-based raw materials via bioconversion; or production using petroleum-based raw materials via bioconversion; or production using bio-based raw materials via chemical methods. The 1,5-pentanediamine of this invention contains organic carbon from a renewable source that conforms to ASTM D6866 standards.

[0016] In some other specific embodiments, the dicarboxylic acid component (B) consists of the following components: (B1) 0 molar proportion of adipic acid, (B2) 0 molar proportion of terephthalic acid, and (B3) 100 molar proportion of aliphatic dicarboxylic acid.

[0017] Preferably, the aliphatic dicarboxylic acid has 10 to 18 carbon atoms, and is preferably selected from at least one of sebacic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, and hexadecanoic acid.

[0018] Preferably, the bio-based polyamide resin PA5X has a relative viscosity of 1.8-2.8; a terminal amine content of 40-60 mmol / kg; and a melting point of 170-320℃, preferably 180-230℃.

[0019] In some other specific embodiments, the dicarboxylic acid component (B) consists of the following components: (B1) 100 molar proportion of adipic acid, (B2) 0 molar proportion of terephthalic acid, and (B3) 0 molar proportion of aliphatic dicarboxylic acid.

[0020] Preferably, the relative viscosity of the bio-based polyamide resin PA56 is 1.9-3.5, more preferably 1.9-2.8; the terminal amino content is 9-60 mmol / kg, more preferably 42-60 mmol / kg; and the melting point is 210-260℃, more preferably 252-260℃.

[0021] In some specific embodiments, the content of the bio-based polyamide resin is 90-98 parts.

[0022] In some specific embodiments, the chain extender is selected from at least one of acid anhydride compounds, epoxy compounds, oxazoline compounds, carbonate compounds, and isocyanate compounds.

[0023] In some specific embodiments, the acid anhydride compounds include, but are not limited to, at least one of pyromellitic dianhydride (PMDA), styrene-maleic anhydride copolymer (SMA), POE-g-MAH, PE-g-MAH, PP-g-MAH, EPDM-g-MAH, and EVA-g-MAH.

[0024] In some specific embodiments, the epoxy compounds include, but are not limited to, at least one of styrene-glycidyl methacrylate oligomers (ADR 4468, ADR 4380, KL-E4300), epoxy polysiloxane (EPM), and triglycidyl isocyanurate (TGIC).

[0025] In some specific embodiments, the oxazoline compounds include, but are not limited to, at least one of bisoxazoline (BOZ), 3-oxazoline, and isoxazoline benzyl ether compounds.

[0026] In some specific embodiments, the carbonate compounds include, but are not limited to, at least one of Brügmann M1251 and M1253.

[0027] In some specific embodiments, the isocyanate compounds include, but are not limited to, at least one of isophorone diisocyanate (IPDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), and polymethylene polyphenyl polyisocyanate (PAPI).

[0028] According to a preferred embodiment of the present invention, the chain extender is selected from at least one of pyromellitic anhydride (PMDA), styrene-maleic anhydride copolymer (SMA), bisoxazoline (BOZ), POE-g-MAH, PP-g-MAH, ADR4468, ADR4380, triglycidyl isocyanate (TGIC), and diphenyltoluene diisocyanate (MDI).

[0029] Preferably, the chain extender is selected from at least one of pyromellitic anhydride (PMDA), styrene-maleic anhydride copolymer (SMA), POE-g-MAH, ADR4468, and ADR4380.

[0030] More preferably, the chain extender is selected from at least two or more combinations of pyromellitic anhydride (PMDA), styrene-maleic anhydride copolymer (SMA), POE-g-MAH, ADR4468, and ADR4380. For example, a combination of ADR4468 and POE-g-MAH, wherein the mass ratio of ADR4468 to POE-g-MAH is preferably 1:(1-3), for example, 1:2. Examples include combinations of styrene-maleic anhydride copolymer (SMA) with POE-g-MAH, ADR4468, or ADR4380. Another example is a combination of pyromellitic anhydride (PMDA) with POE-g-MAH, ADR4468, or ADR4380.

[0031] In some specific embodiments, the content of the chain extender is 1.5-4.5 parts, for example 1.5 parts, 2 parts, 2.5 parts, 3 parts, 4 parts, or 4.5 parts.

[0032] In some specific embodiments, the polyamide material includes an antioxidant, the content of which is 0.05-1 part, more preferably 0.1-0.5 parts.

[0033] In some specific embodiments, the antioxidant is selected from at least one of antioxidant 1098, antioxidant 1010 and antioxidant 168, such as antioxidant 1098.

[0034] In some specific embodiments, the polyamide material includes a heat stabilizer, the content of which is 0.05-1 part, more preferably 0.1-0.5 parts.

[0035] In some specific embodiments, the heat stabilizer includes CuI and / or H10, such as CuI.

[0036] In some specific embodiments, the polyamide material includes a nucleating agent, the content of which is 0.05-5 parts, more preferably 0.5-1 parts.

[0037] In some specific embodiments, the nucleating agent is selected from at least one of calcium carbonate, kaolin, talc, and mica, such as calcium carbonate.

[0038] In some specific embodiments, the polyamide material includes a lubricant, the lubricant content being 0.5-3 parts, more preferably 0.5-1 parts.

[0039] In some specific embodiments, the lubricant is selected from at least one of calcium stearate, magnesium stearate, and polyethylene wax, such as polyethylene wax.

[0040] The present invention also provides a method for preparing the polyamide material as described above, the method comprising the following steps:

[0041] Bio-based polyamide resin, chain extender, antioxidant, heat stabilizer, nucleating agent and lubricant are mixed evenly in proportion, extruded and granulated to obtain a composition, and the composition is subjected to solid-phase polycondensation reaction to obtain polyamide material.

[0042] In some specific embodiments, a high-speed mixer is used to mix the raw materials evenly, with a mixing time of 2-5 minutes, for example, 2 minutes; and a mixing rate of 30-50 rpm, for example, 30 rpm.

[0043] In some specific embodiments, a twin-screw extruder is used for extrusion granulation. Preferably, the twin-screw extruder adopts a six-zone heating mode, with the temperatures of zones one to six being 150-220℃, 200-280℃, 220-280℃, 250-290℃, 270-320℃, and 270-320℃, respectively.

[0044] In some specific embodiments, the extrusion speed is expressed in terms of screw speed, which is 300-550 rpm, for example, 400 rpm.

[0045] In some specific embodiments, the conditions for the solid-state polycondensation reaction include: a temperature of 170-210℃, a vacuum degree of 0-100000Pa, and a reaction time of 8-24h. The solid-state polycondensation reaction of the present invention is carried out in a solid-state thickening oven.

[0046] The types and contents of raw materials such as bio-based polyamide resin, chain extender, antioxidant, heat stabilizer, nucleating agent, and lubricant involved in the preparation method provided by this invention are as described above and will not be repeated here.

[0047] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention. All reagents and raw materials used in the present invention are commercially available.

[0048] Compared with the prior art, the present invention has the following technical effects:

[0049] This invention uses bio-based polyamide resin as raw material. By chain extension modification, the molecular weight of polyamide is increased, the molecular weight distribution is broadened, and the degree of chain segment branching is increased, thereby obtaining a polyamide material with high melt strength and viscosity, which meets the requirements of foaming materials. At the same time, the high bio-based content of the polyamide resin is beneficial to reducing energy consumption and meets the needs of low-carbon economy and sustainable development. Detailed Implementation

[0050] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, all raw materials used are commercially available. Melt strength was obtained by internal mixer testing. Melt viscosity was obtained by Ubbelohde viscometer testing.

[0051] In the following examples and comparative examples: bio-based polyamide 5X resin was purchased from Kaisai (Jinxiang) Biomaterials Co., Ltd.; chain extender was purchased from BASF Group; antioxidant was purchased from BASF Group, Germany; heat stabilizer was purchased from Brügmann AG; nucleating agent was purchased from Liuhe Chemical Co., Ltd.; and lubricant was purchased from Lonza.

[0052] PA56T: The preparation method includes the following steps: (1) Under a nitrogen atmosphere, water, pentanediamine, and dicarboxylic acid (amic acid and terephthalic acid in a molar ratio of 1:1.05) are mixed to prepare a polyamide salt aqueous solution with a concentration of 65wt%; the molar ratio of pentanediamine and dicarboxylic acid is 1.05:1; (2) The polyamide salt aqueous solution is transferred to a polymerization reactor and heated under a nitrogen atmosphere. The temperature inside the reactor rises to 290°C, and the pressure inside the polymerization device rises to 1.6MPa and is maintained for 110 minutes; then, the pressure is reduced to atmospheric pressure within 85 minutes, while the temperature inside the polymerization device is increased to 300°C; a vacuum is drawn to reduce the pressure to -0.05MPa and is maintained for 60 minutes to obtain a melt, which is then stretched and granulated to obtain bio-based polyamide resin PA56T (relative viscosity 2.24, melting point 300°C).

[0053] Example 1

[0054] 97.3 parts of PA56 (melting point 253℃, relative viscosity 2.7, terminal amine content 55mmol / kg), 1.5 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax were weighed. The above raw materials were mixed evenly using a high-speed mixer for 2.5 min at a mixing rate of 35 rpm. The mixture was then fed into a twin-screw extruder using a six-zone heating mode, with zone temperatures of 180℃, 220℃, 250℃, 270℃, 280℃, and 285℃ respectively. The extrusion speed was 400 rpm, expressed as screw speed. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 210℃ and a vacuum of 10000 Pa for 12 h to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0055] Example 2

[0056] Weigh out 97.3 parts of PA510 (melting point 217℃, relative viscosity 2.51, terminal amino group 54mmol / kg), 1.5 parts of chain extender pyromellitic anhydride (PMDA), 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax. Mix the above raw materials evenly using a high-speed mixer for 2.5 min at a mixing rate of 30 rpm. Then, feed the mixture into a twin-screw extruder using a six-zone heating mode. The temperatures of zones one through six are 180℃, 220℃, 250℃, 260℃, 270℃, and 275℃, respectively. The extrusion speed is 400 rpm, expressed as screw speed. Granulate the mixture by twin-screw extrusion to obtain the composition. React the composition at 180℃ and a vacuum of 10000 Pa for 12 h to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0057] Example 3

[0058] 96.3 parts of PA511 (melting point 209℃, relative viscosity 2.47, terminal amino group 52mmol / kg), 2.5 parts of chain extender ADR4380, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax were weighed. The above raw materials were mixed evenly using a high-speed mixer for 2 minutes at a mixing rate of 30 rpm. The mixture was then fed into a twin-screw extruder using a six-zone heating mode, with zone temperatures of 180℃, 220℃, 250℃, 270℃, 270℃, and 275℃ respectively. The extrusion speed was 400 rpm, expressed as screw speed. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 180℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0059] Example 4

[0060] 97.6 parts of PA512 (melting point 210℃, relative viscosity 2.32, terminal amino group 56 mmol / kg), 1.2 parts of chain extender bisoxazoline (BOZ), 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax were weighed. The above raw materials were mixed evenly using a high-speed mixer for 3 minutes at a mixing rate of 40 rpm. The mixture was then fed into a twin-screw extruder using a six-zone heating mode, with zone temperatures of 180℃, 220℃, 250℃, 265℃, 270℃, and 275℃ respectively. The extrusion speed was 400 rpm, expressed as screw speed. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 180℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0061] Example 5

[0062] 97.3 parts of PA513 (melting point 197℃, relative viscosity 2.38, terminal amino group 41 mmol / kg), 1.5 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax were weighed. The above raw materials were mixed evenly using a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. The mixture was then fed into a twin-screw extruder using a six-zone heating mode, with zone temperatures of 180℃, 220℃, 250℃, 260℃, 270℃, and 280℃ respectively. The extrusion speed was 400 rpm, expressed as screw speed. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 170℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0063] Example 6

[0064] Weigh out 96.8 parts of PA514 (melting point 205℃, relative viscosity 2.29, terminal amino group 48mmol / kg), 2.0 parts of chain extender diphenyltoluene diisocyanate (MDI), 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax. Mix the above raw materials evenly in a high-speed mixer for 2 minutes at a mixing rate of 40 rpm. Then, feed the mixture into a twin-screw extruder using a six-zone heating mode. The temperatures of zones one through six are 180℃, 220℃, 250℃, 270℃, 273℃, and 275℃, respectively. The extrusion speed is 400 rpm, expressed as screw speed. Granulate the mixture by twin-screw extrusion to obtain the composition. React the composition at 180℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0065] Example 7

[0066] Weigh out 94.8 parts of PA515 (melting point 191℃, relative viscosity 2.25, terminal amino 51mmol / kg), 4 parts of chain extender styrene-maleic anhydride copolymer (SMA), 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax. Mix the above raw materials evenly in a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. Then, feed the mixture into a twin-screw extruder using a six-zone heating mode. The temperatures of zones one through six are 180℃, 220℃, 250℃, 270℃, 275℃, and 280℃, respectively. The extrusion speed is 400 rpm, expressed as screw speed. Granulate the mixture by twin-screw extrusion to obtain the composition. React the composition at 170℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0067] Example 8

[0068] 97.3 parts of PA516 (melting point 192℃, relative viscosity 2.13, terminal amino group 47mmol / kg), 1.5 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax were weighed. The above raw materials were mixed evenly using a high-speed mixer for 2 minutes at a mixing rate of 35 rpm. The mixture was then fed into a twin-screw extruder using a six-zone heating mode, with zone temperatures of 180℃, 220℃, 250℃, 270℃, 280℃, and 285℃ respectively. The extrusion speed was 400 rpm, expressed as screw speed. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 170℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0069] Example 9

[0070] Weigh out 94.3 parts of PA513 (melting point 197℃, relative viscosity 2.38, terminal amino group 41mmol / kg), 1.5 parts of chain extender ADR4468, 3 parts of POE-g-MAH, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax. Mix the above raw materials evenly in a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. Then, feed the mixture into a twin-screw extruder using a six-zone heating mode. The temperatures of zones one through six are 180℃, 220℃, 250℃, 260℃, 270℃, and 280℃, respectively. The extrusion speed is 400 rpm, expressed as screw speed. Granulate the mixture by twin-screw extrusion to obtain the composition. React the composition at 170℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0071] Example 10

[0072] Weigh out 97.3 parts of PA56T, 1.5 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax. Mix the above raw materials evenly using a high-speed mixer for 2.5 min at a mixing speed of 30 rpm. Then, feed the mixture into a twin-screw extruder using a six-zone heating mode. The temperatures of zones one through six are 220℃, 270℃, 280℃, 290℃, 300℃, and 310℃, respectively. The extrusion speed is 400 rpm, expressed as screw speed. Granulate the mixture using the twin-screw extruder to obtain the composition. React the composition at 210℃ and a vacuum of 10000 Pa for 12 h to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0073] Comparative Example 1

[0074] 98.8 parts of PA513 (melting point 197℃, relative viscosity 2.38, terminal amino group 41 mmol / kg), 10980.1 parts of antioxidant, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax were weighed. The above raw materials were mixed evenly using a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. The mixture was then fed into a twin-screw extruder using a six-zone heating mode. The temperatures of zones one through six were 180℃, 220℃, 250℃, 260℃, 270℃, and 280℃, respectively. The extrusion speed was 400 rpm, expressed as screw speed. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 170℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0075] Comparative Example 2

[0076] 98.5 parts of PA513 (melting point 197℃, relative viscosity 2.38, terminal amino group 41 mmol / kg), 0.3 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax were weighed. The above raw materials were mixed evenly using a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. The mixture was then fed into a twin-screw extruder using a six-zone heating mode, with zone temperatures of 180℃, 220℃, 250℃, 260℃, 270℃, and 280℃ respectively. The extrusion speed was 400 rpm, expressed as screw speed. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 170℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0077] Comparative Example 3

[0078] 92.8 parts of PA513 (melting point 197℃, relative viscosity 2.38, terminal amino group 41mmol / kg), 6 parts of chain extender ADR44686, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax were weighed. The above raw materials were mixed evenly using a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. The mixture was then fed into a twin-screw extruder using a six-zone heating mode, with zone temperatures of 180℃, 220℃, 250℃, 260℃, 270℃, and 280℃ respectively. The extrusion speed was 400 rpm, expressed as screw speed. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 170℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0079] Comparative Example 4

[0080] Weigh out 97.3 parts of polyamide PA6 (purchased from Xinhui Meda, melting point 223℃, relative viscosity 2.46, terminal amino 54mmol / kg), 1.5 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax. Mix the above raw materials evenly in a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. Then, feed the mixture into a twin-screw extruder with a six-zone heating mode. The temperatures of zones one to six are 180℃, 220℃, 250℃, 270℃, 280℃, and 285℃, respectively. The extrusion speed is 400 rpm. The mixture is granulated by twin-screw extrusion to obtain the composition. React the composition at 180℃ and a vacuum of 10000Pa for 12 hours to obtain the polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0081] Comparative Example 5

[0082] Weigh out 97.3 parts of polyamide PA66 (purchased from DuPont, relative viscosity 2.6, terminal amine content 48 mmol / kg, melting point 260℃), 1.5 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax. Mix the above raw materials evenly in a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. Then, feed the mixture into a twin-screw extruder with a six-zone heating mode. The temperatures of zones one to six are 180℃, 220℃, 250℃, 260℃, 270℃, and 280℃, respectively. The extrusion speed is 400 rpm. The mixture is granulated by twin-screw extrusion to obtain the composition. React the composition at 180℃ and a vacuum of 10000 Pa for 12 hours to obtain the polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0083] Comparative Example 6

[0084] Weigh out 97.3 parts of PA610 (purchased from Evonik, relative viscosity 2.3, terminal amine content 51 mmol / kg, melting point 220℃), 1.5 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, and heat stabilizer CuI. 0.1 parts of nucleating agent calcium carbonate, 0.5 parts of lubricant polyethylene wax, and the above raw materials were mixed evenly in a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. The mixture was then fed into a twin-screw extruder with a six-zone heating mode. The temperatures of zones one through six were 180°C, 220°C, 250°C, 260°C, 270°C, and 275°C, respectively, expressed as screw speed. The extrusion speed was 400 rpm. The mixture was granulated by twin-screw extrusion to obtain the composition. The composition was reacted at 180°C and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0085] Comparative Example 7

[0086] Weigh out 97.6 parts of PA612 (purchased from DuPont, relative viscosity 2.0, terminal amine content 43 mmol / kg, melting point 211℃), 1.2 parts of chain extender ADR4468, 0.1 parts of antioxidant 1098, 0.1 parts of heat stabilizer CuI, 0.5 parts of nucleating agent calcium carbonate, and 0.5 parts of lubricant polyethylene wax. Mix the above raw materials evenly in a high-speed mixer for 3 minutes at a mixing rate of 30 rpm. Then, feed the mixture into a twin-screw extruder with a six-zone heating mode. The temperatures of zones one to six are 180℃, 220℃, 250℃, 260℃, 270℃, and 275℃, respectively. The extrusion speed is 400 rpm. The mixture is granulated by twin-screw extrusion to obtain the composition. React the composition at 180℃ and a vacuum of 10000 Pa for 12 hours to obtain a polyamide material. Its melt strength and viscosity were measured, and the results are shown in Table 1.

[0087] Table 1

[0088]

[0089]

[0090] As shown in Table 1, the relative viscosity and melt strength of the polyamide material were significantly improved through chain extension modification. Specifically, as seen in Example 5 and Comparative Examples 1-3, the amounts of chain extender were 1.5 parts, 0 parts, 0.3 parts, and 6 parts, respectively. Among them, the polyamide material obtained in Comparative Example 3 was insoluble and had a high melt strength; the viscosity and strength of the polyamide materials obtained in Comparative Examples 1-2 were much worse than those in Example 5. It can be seen that the amount of chain extender in the range of 0.5-5 parts can effectively improve the strength and viscosity of polyamide materials, meeting the requirements of foamed materials. As seen in Examples 1-10 and Comparative Examples 5-8, when the polyamide resin is PA6, PA66, PA610, or PA612, the relative viscosity and strength of the polyamide materials obtained are generally inferior to those obtained in Example 1 using PA56, Examples 2-9 using long-chain resins, or Example 10 using PA56T. It is evident that when using PA5X or PA5XT series polyamide resins, the performance of polyamide materials is superior to that of PA6 and PA6X series, and they can better meet the foaming requirements.

[0091] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A polyamide material, characterized in that, The polyamide material comprises the following components in parts by weight: 85-98 parts of bio-based polyamide resin and 0.5-5 parts of chain extender; the bio-based polyamide resin is formed from pentanediamine (A) and dicarboxylic acid component (B), the total of components (A) and (B) being 100 mol%; wherein, the dicarboxylic acid component (B) is composed of the following components: (B1) 0-100 mol% adipic acid, (B2) 0-100 mol% terephthalic acid, (B3) 0-100 mol% other aliphatic dicarboxylic acids besides adipic acid, the total of (B1), (B2) and (B3) being 100 mol%.

2. The polyamide material according to claim 1, characterized in that, The molar ratio of the pentanediamine (A) to the dicarboxylic acid component (B) is (1-1.05):1; and / or The dicarboxylic acid component (B) consists of the following components: (B1) 10-90 molar proportion of adipic acid, (B2) 10-90 molar proportion of terephthalic acid, and (B3) 0 molar proportion of aliphatic dicarboxylic acid.

3. The polyamide material according to claim 2, characterized in that, The dicarboxylic acid component (B) is composed of the following components: (B1) 40-90 molar proportion of adipic acid, (B2) 10-60 molar proportion of terephthalic acid, and (B3) 0 molar proportion of aliphatic dicarboxylic acid. The molar ratio of adipic acid to terephthalic acid is 1:(0.1-1.5); The relative viscosity of the bio-based polyamide resin is 2.05-2.65; the melting point is 260-330℃.

4. The polyamide material according to claim 3, characterized in that, The relative viscosity of the bio-based polyamide resin is 2.24-2.45; the melting point is 270-300℃.

5. The polyamide material according to claim 1, characterized in that, The dicarboxylic acid component (B) is composed of the following components: (B1) 0 molar proportion of adipic acid, (B2) 0 molar proportion of terephthalic acid, and (B3) 100 molar proportion of aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid has 10 to 18 carbon atoms and is selected from at least one of sebacic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, and hexadecanoic acid. The bio-based polyamide resin has a relative viscosity of 1.8-2.8, a terminal amino content of 40-60 mmol / kg, and a melting point of 170-320℃.

6. The polyamide material according to claim 5, characterized in that, The bio-based polyamide resin has a melting point of 170-320℃.

7. The polyamide material according to claim 1, characterized in that, The dicarboxylic acid component (B) is composed of the following components: (B1) 100 molar proportion of adipic acid, (B2) 0 molar proportion of terephthalic acid, and (B3) 0 molar proportion of aliphatic dicarboxylic acid. The bio-based polyamide resin has a relative viscosity of 1.9-3.5; a terminal amino content of 9-60 mmol / kg; and a melting point of 210-260℃.

8. The polyamide material according to claim 1, characterized in that, The bio-based polyamide resin has a relative viscosity of 1.9-2.8, a terminal amino content of 42-60 mmol / kg, and a melting point of 252-260℃.

9. The polyamide material according to any one of claims 1-8, characterized in that, The chain extender is selected from at least one of acid anhydride compounds, epoxy compounds, oxazoline compounds, carbonate compounds, and isocyanate compounds; The acid anhydride compound is selected from at least one of pyromellitic dianhydride (PMDA), styrene-maleic anhydride copolymer (SMA), POE-g-MAH, PE-g-MAH, PP-g-MAH, EPDM-g-MAH, and EVA-g-MAH; and / or The epoxy compound is selected from at least one of styrene-glycidyl methacrylate oligomers, epoxy polysiloxanes (EPM), and triglycidyl isocyanurate (TGIC); and / or The oxazoline compound is selected from at least one of bisoxazoline (BOZ), 3-oxazoline, and isoxazoline benzyl ether compounds; and / or The carbonate compound is Brügmann M1251 and / or M1253; and / or The isocyanate compound is selected from at least one of isophorone diisocyanate IPDI, toluene diisocyanate TDI, diphenylmethane diisocyanate MDI, dicyclohexylmethane diisocyanate HMDI, hexamethylene diisocyanate HDI and polymethylene polyphenyl polyisocyanate PAPI. And / or, the content of the chain extender is 1.5-4.5 parts.

10. The polyamide material according to claim 9, characterized in that, The styrene-glycidyl methacrylate oligomers include one or more of ADR 4468, ADR 4380, and KL-E4300.

11. The polyamide material according to claim 9, characterized in that, The chain extender is selected from at least one of pyromellitic anhydride PMDA, styrene-maleic anhydride copolymer SMA, bisoxazoline BOZ, POE-g-MAH, PP-g-MAH, ADR4468, ADR4380, triglycidyl isocyanate TGIC, and diphenyltoluene diisocyanate MDI.

12. The polyamide material according to claim 11, characterized in that, The chain extender is selected from at least one of pyromellitic anhydride PMDA, styrene-maleic anhydride copolymer SMA, POE-g-MAH, ADR4468, and ADR4380.

13. The polyamide material according to claim 12, characterized in that, The chain extender is selected from at least two or more combinations of pyromellitic anhydride PMDA, styrene-maleic anhydride copolymer SMA, POE-g-MAH, ADR4468 and ADR4380.

14. The polyamide material according to any one of claims 1-8, characterized in that, The polyamide material includes an antioxidant, and the content of the antioxidant is 0.05-1 part; The antioxidant is selected from at least one of antioxidant 1098, antioxidant 1010, and antioxidant 168; And / or, the polyamide material includes a heat stabilizer, the content of which is 0.05-1 part; The heat stabilizer includes CuI and / or H10; And / or, the polyamide material includes a nucleating agent, the content of which is 0.05-5 parts; The nucleating agent is selected from at least one of calcium carbonate, kaolin, talc, and mica powder; And / or, the polyamide material includes a lubricant, the lubricant content being 0.5-3 parts; The lubricant is selected from at least one of calcium stearate, magnesium stearate, and polyethylene wax.

15. The polyamide material according to claim 14, characterized in that, The antioxidant content is 0.1-0.5 parts; and / or, The content of the heat stabilizer is 0.1-0.5 parts; and / or, The nucleating agent is present in a concentration of 0.5-1 part; and / or, The content of the lubricant is 0.5-1 part.

16. A method for preparing a polyamide material according to any one of claims 1-15, characterized in that, The method includes the following steps: Bio-based polyamide resin, chain extender, antioxidant, heat stabilizer, nucleating agent and lubricant are mixed evenly in proportion, extruded and granulated to obtain a composition, and the composition is subjected to solid-phase polycondensation reaction to obtain polyamide material.

17. The method according to claim 16, characterized in that, Extrusion granulation is performed using a twin-screw extruder, which employs a six-zone heating mode, with zone one through six having temperatures of 150-220℃, 200-280℃, 220-280℃, 250-290℃, and 270-320℃ respectively; and / or The extrusion speed is 300-550 rpm, expressed in terms of screw speed.

18. The method according to claim 16 or 17, characterized in that, The conditions for the solid-phase polycondensation reaction include: a temperature of 170-210℃, a vacuum of 0-100000Pa, and a reaction time of 8-24h.

Citation Information

Patent Citations

  • Polyamide 5X resin capable of rapidly crystallizing and preparation method thereof

    CN111518269A

  • Process for increasing the melt strength of a thermoplastic polymer

    EP3246349A1

  • Method for preparing extruded polyamide foams

    US20200317878A1